Long-term persistence of the floating bull kelp Durvillaea antarctica from the South-East Pacific: Potential contribution to local and transoceanic connectivity - Tala, Fadia; Lopez, Boris A.; Velasquez, Marcel; Jeldres, Ricardo; Macaya, Erasmo C.; Mansilla Muñoz, Andres Omar; Ojeda Villarroel, Jaime Andrés; Thiel, Martin (My University, 2019)
Current knowledge about the performance of floating seaweeds as dispersal vectors comes mostly from mid latitudes (30 degrees-40 degrees), but phylogeographic studies suggest that long-distance dispersal (LDD) is more common at high latitudes (50 degrees-60 degrees). To test this hypothesis, long-term field experiments with floating southern bull kelp Durvillaea antarctica were conducted along a latitudinal gradient (30 degrees S, 37 degrees S and 54 degrees S) in austral winter and summer. Floating time exceeded 200d in winter at the high latitudes but in summer it dropped to 90d, being still higher than at low latitudes (< 45d). Biomass variations were due to loss of buoyant fronds. Reproductive activity diminished during long floating times. Physiological changes included mainly a reduction in photosynthetic (F-v/F-m and pigments) rather than in defence variables (phlorotannins and antioxidant activity). The observed long floating persistence and long-term acclimation responses at 54 degrees S support the hypothesis of LDD by kelp rafts at high latitudes.
Keywords: chile; durvillaea antarctica; floating persistence; rafting; dispersal; floating seaweeds; temperature